Thermal-pressure simulation experiment of pore evolution of Upper Ordovician shale in Baltic Basin - Chuxiong LI; Baojian SHEN; Anyang PAN; Wentao ZHANG; Ang LI; Jianghui DING (Shiyou shiyan dizhi, 2020)
Most of the marine shale in South China is highly over mature and the pore evolution history cannot be determined. The Upper Ordovician shale in the Baltic Basin in Europe was selected to conduct a laboratory thermal-pressure simulation experiment to emulate geological conditions in order to reveal the evolution and distribution of marine shale pores. The evolution characteristics and formation mechanism of the experimental shale pores during the maturation of organic matter were systematically explained based on the organic petrological characteristics of the raw shale samples, the quantitative statistics of the simulated products, and the scanning electron microscopy analysis. The development of the overall shale pores increases with the increase of the thermal evolution of organic matter. The pores tend to communicate with each other, and gradually evolve from the initial undeveloped state to a complex and interlaced pore network. Organic and inorganic pores are subdivided into 8 categories according to their morphology and origin: spongy organic matter (OM), shrinkage OM, bubble OM, mold, mineral dissolution, intergranular, clay mineral interlayer and modified mineral pores. The transformation degree of organic matter and the primary migration of oil and gas are influenced by the difference of organic macerals. The distribution of organic matter pores showed a strong heterogeneity, and the development of inorganic mineral pores occurred in stages. The effective preservation of pores needs special attention during the shale gas exploration in the high evolution stage.